Teaching learning-based optimisation algorithm: a survey. (20th October 2020) - Mishra, Ruchi; Sharma, Nirmala; Sharma, Harish
In recent years swarm intelligence (SI)-based techniques have proven their importance for finding the solution of global optimisation problems. In SI-based algorithms agents act in a group and learn from each other for food foraging surviving, etc. Teaching-learning-based optimisation algorithm (TLBOA) is an efficient approach of dealing with linear, nonlinear and multi-dimensional optimisation problems established by Dr. R. Venkata Rao in 2011. Since its inception, a lot of research has been carried out to make TLBOA more proficient and to apply it to different types of optimisation problems. This paper presents a review of TLBOA developments, applications, comparative-performance, and future research perspectives.